2019
DOI: 10.1094/php-11-18-0077-rs
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Occurrence, Distribution, and Population Densities of Plant-Parasitic Nematodes in the Pacific Northwest of the United States from 2012 to 2016

Abstract: The Pacific Northwest (PNW) of the United States (Idaho, Oregon, and Washington) is a diverse agricultural production area with over 400 different commodities grown in the region. Plant-parasitic nematodes are a constraint to the production of many of these commodities. Soil sample data from 2012 to 2016 were obtained from nematode diagnostic laboratories in the region to assess trends in occurrence, population densities, and distribution of plant-parasitic nematodes in the PNW. A total of 38,022 unique data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…In Washington State, these species were detected together on golf course greens in ratios of approximately 4:1. In a study of nematodes identified by diagnostic laboratories in the Pacific Northwest (Zasada et al, 2019), M. naasi was found in fewer than 1% of samples, making them much less common than M. chitwoodi (found in 71% Supplementary Table S1. Continued…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Washington State, these species were detected together on golf course greens in ratios of approximately 4:1. In a study of nematodes identified by diagnostic laboratories in the Pacific Northwest (Zasada et al, 2019), M. naasi was found in fewer than 1% of samples, making them much less common than M. chitwoodi (found in 71% Supplementary Table S1. Continued…”
Section: Resultsmentioning
confidence: 99%
“…This species is one of the most important root-knot nematodes (RKN) affecting monocots, and is known to cause reduced growth and vigor in turfgrasses (Bélair et.al., 2006). This species has a wide distribution, having been reported in the United States in several states, as well as in Canada, South America and Europe (Zeng et al, 2012). A report from 2012, in which authors surveyed 238 golf courses from 10 states across the western United States, found RKN in 60% of the samples (McClure et.al.…”
mentioning
confidence: 99%
“…Once a vineyard is heavily infested with M. hapla or M. xenoplax , newly planted vines may suffer, limiting establishment success and delaying time to first harvest and subsequent yield (Forge et al., 2021; Zasada, Kitner et al., 2019). While both M. hapla and M. xenoplax are found in both Washington and Oregon, M. hapla is the most prevalent nematode pest of eastern Washington vineyards, and M. xenoplax is the most prevalent nematode pest of western Oregon vineyards (Pinkerton et al., 1999; Zasada et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In some cropping systems, PPN are the dominant plant-pathogens of any kind (Savary et al, 2019). Thus, NDL receive a large number of samples ( Zasada et al, 2019 ) from farmers and agricultural consultants for the diagnosis and identification of PPN present in their fields. This information is critical for developing effective management strategies to control the nematode population, spread of nematodes, and minimize economic losses.…”
mentioning
confidence: 99%